Hemolysis indexes for biochemical tests and immunoassays on Roche analyzers: Determination of allowable interference limits according to different calculation methods. (April 2015) - Monneret, Denis; Mestari, Fouzi; Atlan, Gregory; Corlouer, Camille; Ramani, Zo; Jaffre, Jeremy; Dever, Sylvie; Fressart, Veronique; Alkouri, Rana; Lamari, Foudil; Devilliers, Catherine; Imbert-Bismut, Françoise; et al.
Abstract Objectives. To determine the hemolysis interference on biochemical tests and immunoassays performed on Roche Diagnostics analyzers, according to different maximum allowable limits. Design and methods. Heparinized plasma and serum pools, free of interferences, were overloaded by increasing amounts of a hemoglobin-titrated hemolysate. This interference was evaluated for 45 analytes using Modular® and Cobas® analyzers. For each parameter, the hemolysis index (HI) corresponding to the traditional ± 10% change of concentrations from baseline (± 10%Δ) was determined, as well as those corresponding to the analytical change limit (ACL), and to the reference change value (RCV). Then, the relative frequencies distribution (% RFD) of hemolyzed tests performed in a hospital laboratory over a 25-day period were established for each HI as allowable limit. Results. Considering the ± 10%Δ, the analyte concentrations enhanced by hemolysis were: Lactate dehydrogenase (LDH), aspartate aminotransferase (AST), folate, potassium, creatine kinase, phosphorus, iron, alanine aminotransferase, lipase, magnesium and triglycerides, decreasingly. The analyte concentrations decreased by hemolysis were: Haptoglobin, high-sensitive troponin T and alkaline phosphatase. Over the 25-day period, the % RFD of tests impacted more than 10%Δ by hemolysis were < 7% for LDH; < 5% for AST, folates and iron; and < 1% for the other analytes. Considering the ACL, HI were lower, giving % RFD substantially increased for many analytes, whereas only four analytes remain sensitive to hemolysis when considering RCV. Conclusion. This study proposes new HI based on different allowable limits, and can therefore serve as a starting point for future harmonization of hemolysis interference evaluation needed in routine laboratory practice.